The Efficacy and Safety of Probiotics for Allergic Rhinitis: A Systematic Review and Meta-Analysis - Luo, Chao; Peng, Shunlin; Li, Mao; Ao, Xudong; Liu, Zhiqing (Frontiers in Immunology, 2022)
Background: Probiotics have proven beneficial in a number of immune-mediated and allergic diseases. Several human studies have evaluated the efficacy and safety of probiotics in allergic rhinitis, however, evidence for their use has yet to be firmly established. Objective: We undertook a systematic review and meta-analysis aiming to address the effect and safety of probiotics on allergic rhinitis. Methods: We systematically searched databases (MEDLINE (PubMed), Embase, the Cochrane Central Register of Controlled Trials) from inception until June 1, 2021. Qualified literature was selected according to inclusion and exclusion criteria, extracted the data, and conducted a systematic review and meta-analysis. Results：28 studies were included. The results showed probiotics significantly relieved allergic rhinitis symptoms (SMD -0.86, 95% CI [ -1.48, -0.24]; p=0.006, I2 = 89%), decrease RQLQ scores compared with control group (SMD, -2.38,95% CI [-3.58, -1.19], P<0.0001, I2=97%), and increase Th1/Th2 ratio (SD, -2.01,95%CI [-3.94, -0.08], P=0.04, I2=72%). There was no significant change in overall or specific IgE levels between probiotic-treated and placebo-treated subjects (SMD,0.09,95%CI, [-0.16, 0.34], I2=0%, SMD, -0.03,95%CI, [-0.18, 0.13], p=0.72, I2=0%, respectively). Conclusions: To sum up, probiotic supplement seems to be effective in ameliorating allergic rhinitis symptoms and improving the quality of life, but there is high heterogeneity in some results after subgroup analysis and clinicians should be cautious when recommending probiotics in treating AR. Systematic review registration: PROSPERO (CRD42021242645)